F.R. David - What I mean is. - Holder, Will; Aiello, Rosa; Collins, Jean; Hayward, Danny; Hiller, Susan; Mayer, Bernadette; Myles, Eileen; Poggenpohl, Sharon, H.; Robertson, Lisa; Visible, Language; Wojnarowicz, David; Wright, Edward; et al. ([S.l.] : uh books, 2018)
McLuskey, Emmie ; Gruijthuijsen, Krist ; Knox, Bitsy ; Antoine, Jean-Philippe; David ; Fischli, Fredi ; Olsen, Niels ; Schiferli, Teo ; Birch, Jesse ; Samuel, Daphne ; Trinier, Kristy ; Wills, Camilla ; Sperlinger, Mike ; Wright, Seymour ; Skaer, Lucy ; Giblin, Tessa ; Watson, Grant ; von Osten, Marion ; Fallon, Stuart
The Art of Sience Writing, Darwin, Freud, Einstein, Rachel Carlson, Jane Goodall, Lewis carroll, writing experiments, annotated bibliograpy on science writing
boek